A RETURN AND VOLATILITY CHARACTERISTICS OF COSMETIC COMPANY STOCKS IN INDONESIA (2022–2024): A DESCRIPTIVE ANALYSIS - Ditya, Ni Nyoman; Suli Asmara Yanti, Ni Nyoman (Jurnal Ilmu Manajemen (JIMMU), 2025)
ABSTRACT The capital market plays a vital role in economic development by facilitating investment opportunities and enabling efficient capital allocation. Indonesia’s cosmetic industry has shown notable growth in recent years, driven by increasing consumer demand and changing lifestyle preferences. Despite this growth, empirical research on return, volatility, and return distribution of cosmetic stocks remains limited, making the sector underexplored. This study analyzes the return, volatility, and distribution patterns of five cosmetic companies listed on the Indonesia Stock Exchange during 2022–2024, namely MBTO, MRAT, VICI, KINO, and UNVR, providing a comprehensive assessment of stock performance and risk exposure. A quantitative descriptive approach was employed using secondary data of daily closing stock prices obtained from IDX. Data were analyzed with SPSS, calculating daily returns, annual averages, standard deviations to measure volatility, and skewness and kurtosis examined return distributions. Descriptive statistics identified performance patterns and assessed risk characteristics across companies, ensuring objective measurement of financial performance and evaluation of risk-return dynamics, findings indicate heterogeneous stock performance. MRAT recorded the highest average return in 2022 but declined in subsequent years, while MBTO and VICI maintained relatively stable yet modest positive returns. KINO and UNVR consistently showed negative trends. MBTO exhibited the highest volatility, reflecting greater exposure to price fluctuations. Most return distributions deviated from normality, as indicated by positive skewness and high kurtosis, implying potential for extreme gains or losses, these results show that Indonesia’s cosmetic stock market presents both investment opportunities and substantial risks, highlighting the need for careful risk-return assessment. The study provides practical insights for investors in portfolio management and risk mitigation, and valuable information for policymakers and stakeholders seeking to understand this expanding consumer-driven sector. Moreover, the findings contribute to literature on emerging market stock behavior, showing how internal financial performance and external market conditions shape return and volatility patterns.